Macroinvertebrates as indicators of human disturbances on sandy beaches: a global review - Costa, L., Zalmon, I., Fanini, L.; Defeo, O. (My University, 2020)
Sandy beaches are ecosystems under increasing human pressure that require efficient management and conservation strategies. Resident macroinvertebrates usually respond to disturbances by changing their behaviour and abundance, and therefore they may be used as indicator species using simple and low-cost monitoring strategies. We synthesize information from the scientific literature on the use of sandy beach macroinvertebrates as indicators of human disturbances operating at local scales. Response ratios were applied to perform a meta-analysis supported by empirical data to objectively assess the magnitude of human disturbances on beach fauna. The &ldquocompare and contrast” approach represented some 80% of the studies. Gradient assessments were performed by 16% of the studies, though without determining thresholds of disturbance. Long-term monitoring (encompassing more than two years) was the general approach used in studies about harvesting, but it was not used when assessing other type of disturbances. Causality relationships and mechanisms underlying impacts were rarely assessed. Useful indicators to specific human disturbances were: 1) ghost crabs, which indicate the negative effects of vehicle traffic and nourishment 2) talitrids as indicators of trampling and mechanical cleaning and 3) clams as indicators of harvesting. As beaches are affected by multiple stressors acting simultaneously, the relative importance of each one has been difficult to reveal. It remains a priority to identify how different human disturbances are affecting macroinvertebrates under a range of diffuse impacts. Such results would allow for the depiction of patterns and future studies should prioritize gradient analyses and manipulative experiments to provide thresholds of specific stressors and mechanisms of impacts. Highlights The use of beach macroinvertebrates as indicators of human impacts was reviewed. Response ratios of multiple metrics to disturbances were applied on a global scale. Single-species responses performed better than aggregate descriptors in detecting impacts. Reliable response ratios to specific impacts was difficult to reveal by single taxa. Impact assessments must rely on the use of several indicator species and metrics.
Keywords: Bioindicator; Biomonitor; Ecological indicator; Human impact; Invertebrates; Monitoring; Meta-analysis